DETERMINAN SIBLING RIVALRY DENGAN KNOWLEDGE ORANG TUA PADA ANAK TAHAP PRA OPRASIONAL - Redya Ayu Fernanda (Midwifery Science Care Journal, 2024)
Background: When a child is anticipating the birth or presence of a sibling, they frequently experience sibling rivalry. Sibling rivalry in children at the pre-operational stage will tend to be excessive because children still think egocentrically during the pre-operational stage, and their emotional regulation is unstable. This study aimed to determine the relationship between sibling rivalry and parents' knowledge in pre-operational stage children at Kindergarten Cahya Indria Demak. The population in this study were parents who had pre-operational-stage children attending Kindergarten Cahya Indria Demak, with a total of 144 people who obtained a sample of 96 people. This research method used a cross-sectional approach with a correlational analytic design. Sampling uses a purposive sampling technique. The instruments used in this study were a sibling rivalry questionnaire and a parental knowledge questionnaire. Data analysis uses Spearman rank. The results of the study showed a p-value of 0.000, so if a p-value of (0.000) < (0.05), then Ha is accepted and H0 is rejected, with an R-value of (-0.707), meaning that there is a strong and significant relationship between sibling rivalry events and parental knowledge. It has a negative value, which means that parents' knowledge about sibling rivalry is good if there is no sibling rivalry. If the incidence of sibling rivalry is high, then parents' knowledge about sibling rivalry is lacking. The conclusion is based on statistical tests that a relationship exists between sibling rivalry and parents' knowledge in pre-operational stage children. Based on research, parents are expected to pay more attention to caring for their brothers and sisters so that sibling rivalry does not occur.